2015
DOI: 10.1007/s11420-014-9421-9
|View full text |Cite
|
Sign up to set email alerts
|

Onlay Tibial Implants Appear to Provide Superior Clinical Results in Robotic Unicompartmental Knee Arthroplasty

Abstract: Background: Unicompartmental knee arthroplasty (UKA) is an increasingly popular option for the treatment of single-compartment knee osteoarthritis (OA) in adults. Two options for tibial resurfacing during UKA are (1) allpolyethylene inlays and (2) metal-backed onlays. Questions/ Purposes: The aim of this study was to determine whether there are any differences in clinical outcomes with inlay versus onlay tibial components. Patients and Methods: We identified 39 inlays and 45 onlays, with average 2.7-and 2.3-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Fixed bearing designs have been shown in several studies to have equivalent clinical and radiographic outcomes compared to mobile-bearing implant designs at mid and long term follow up [15]. A fixed bearing eliminates the risk of bearing dislocation, however some studies have shown higher revision rates for all-polyethylene tibial components compared to those that utilize metal-backed implants [16][17][18]. Clear advantage of this implant is low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed bearing designs have been shown in several studies to have equivalent clinical and radiographic outcomes compared to mobile-bearing implant designs at mid and long term follow up [15]. A fixed bearing eliminates the risk of bearing dislocation, however some studies have shown higher revision rates for all-polyethylene tibial components compared to those that utilize metal-backed implants [16][17][18]. Clear advantage of this implant is low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have assessed functional outcomes of inlay and onlay components. Gladnick et al compared inlay versus onlay components at the 2-year follow-up [ 19 ]. Patients in their study underwent, similar to this current study, robotic-assisted UKA surgery, and the authors also reported superior WOMAC scores in patients undergoing metal-backed.…”
Section: Discussionmentioning
confidence: 99%
“…1 a) whereas onlay components are cemented on top of the flat tibial cut with a metal baseplate and therefore rely on the cortical bone as well as on the subchondral bone (Fig. 1 b) [ 19 , 43 ]. Studies have shown that inlay components have higher peak stress at the tibial surface compared to onlay components [ 49 , 61 ], which could be explained by the fact that onlay components rest on the cortical bone and that the metal backing distributes forces over the tibia [ 49 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we extended the research to the reference list of all relevant articles. At this point, a stepwise exclusion of studies not meeting aforementioned inclusion criteria was conducted, such as studies comparing biomechanical behavior in knee model, 11,12 comparative data of implants with different geometry (onlay vs inlay), [14][15][16] and studies with follow-up < 24 months (►Fig. 1); moreover, no data from national registries were included, 8,17 to minimize possible bias, such as different implant design, cementation technique, and surgeons' experience.…”
Section: Search Strategy and Data Collectionmentioning
confidence: 99%